Leadership behavior : structural relationship of emotional intelligence (self awareness, self management, social awareness and relationship management) among public school personnel in Malaysia - Nurul Hudani Md Nawi; Marof Redzuan; Puteri Hayati Megat Ahmad; Shazia Iqbal Hashmi (2016)
Various changes in the educational system have evolved for educator leaders recently. However, negative impacts on leader’s emotional intelligence due to leadership behavior that arise problems in producing good quality of work can have significant effect on their performance. This study investigates the impact of an emotional intelligence on leadership behaviour aswell as fitness of the suggested hypothetical model and the observed data. Using a structured questionnaire derived from the literature, data were collected from 306 (89%) subjects from a 15 SBT (High Performance Schools) in Malaysia which were chosen by cluster sampling procedur. the data were then analyzed using structural equation modeling (SEM); an acceptable level of model fit was found. Two sets of questionnaire to measure emotional intelligence (Emotional Competence Inventory) (ECI) and leadership behavior (Multi-factor leadership questionnaires (MLQ) were administered. The inclusion criteria consisted of leaders in a school setting. Results: Three and-six educator leaders from fifteen SBT schools in Malaysia were recruited into the study. Respondents were on average 41 years old (range= 26-60 years). The Majority were female (n=174), education level (degree; n=255), and working experience (range=11-20 years; n=107. In examining the relationship between emotional intelligence with leadership behavior, EQ was positively related to transformational leadership, p < 0.001, R2 = 0.61, and transactional leadership, p< 0.001, R2 = 0.77. The result shows that the model fit indices demonstrates TLI (Tucker Index), NFI (Normed Fit), RFI (Relative Fit Index), IFI (Incremental Fit Index) and CFI (Comparative Fit Index) are more than .90 (from .932 until .975), RMSEA (Root Mean Square Error of Approximation) also shows 0.055 (RMSEA <. 08) (Byrne, 2001). These values indicate an adequate fit and it’s obviously met the basic requirment of model fit. The values of the Chi-Squared Roots Goodness of Fit also show 1.87, below 3. Therefore, the model is significantly fit and support to the data. On a practical note, the assessment of psychological constructs in school setting eg; EQ and leadership could possibly assist in enhancing the work performances in delivering huge benefits to the society especially in the educational contexts.